2005
DOI: 10.1139/g05-055
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci controlling agronomic traits in the spring wheat cross RL4452 × 'AC Domain'

Abstract: Relatively little is known about the genetic control of agronomic traits in common wheat (Triticum aestivum L.) compared with traits that follow Mendelian segregation patterns. A doubled-haploid population was generated from the cross RL4452x'AC Domain' to study the inheritance of the agronomic traits: plant height, time to maturity, lodging, grain yield, test weight, and 1000-grain weight. This cross includes the genetics of 2 western Canadian wheat marketing classes. Composite interval mapping was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
170
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(219 citation statements)
references
References 56 publications
42
170
3
4
Order By: Relevance
“…A region involving three QTL at position 33-36 cM on 3D detected in E1, E3 and E4 (Fig. 6) co-incided with previous studies (McCartney et al 2005;Somers et al 2004). Two QTL for TKW on 7A shared the same marker interval with QTL reported in previous studies, suggesting the existence of a locus for TKW in this region (Fig.…”
Section: Relationship Between Stay-green and Agronomic Traitssupporting
confidence: 83%
See 1 more Smart Citation
“…A region involving three QTL at position 33-36 cM on 3D detected in E1, E3 and E4 (Fig. 6) co-incided with previous studies (McCartney et al 2005;Somers et al 2004). Two QTL for TKW on 7A shared the same marker interval with QTL reported in previous studies, suggesting the existence of a locus for TKW in this region (Fig.…”
Section: Relationship Between Stay-green and Agronomic Traitssupporting
confidence: 83%
“…A cluster for PH and TKW on 4D (Fig. 3) was reported in other studies (McCartney et al 2005;Huang et al 2006;Wang et al 2009). There were one QTL for NDVI and four QTL for CC at this locus, harboring QTL for plant height.…”
Section: Qtl Clustering and Pleiotropysupporting
confidence: 81%
“…Comparative analysis with the known major QTL for yield in wheat: A survey of the literature reporting QTL for GY and related agronomic traits in both tetraploid and hexaploid wheat (Li et al 2002;Peng et al 2003;Elouafi and Nachit 2004;Huang et al 2004Huang et al , 2006McCartney et al 2005;Quarrie et al 2005Quarrie et al , 2007Marza et al 2006;Narasimhamoorthy et al 2006;Kuchel et al 2007;Kumar et al 2007;Ma et al 2007) revealed rather different scenarios for the two major GY QTL identified in our study. Our comparative analysis was carried out by relating the (LOD À 1) supporting interval of the QTL to the Ta-SSR-2004 consensus map (Somers et al 2004).…”
Section: Discussionmentioning
confidence: 55%
“…2BL (Bö rner et al 2002;Marza et al 2006), and QTL for GY, kernel weight, and number of kernels per spike have been reported on chr. 2AL (Bö rner et al 2002;Peng et al 2003;Huang et al 2004;McCartney et al 2005), but not in the distal region. Conversely, major QTL for GY have been identified in two different genetic backgrounds (Bö rner et al 2002;Campbell et al 2003) on the short distal regions of chr.…”
Section: Discussionmentioning
confidence: 99%
“…5. A QTL for GY was mapped to 4AS near marker wmc48 (McCartney et al 2005b). Our complete map (supplemental Figure S4 at http://www.genetics.org/ supplemental/) shows wmc48 to be located 13.4 cM from wPt2788 ( Figure 2d) and significantly associated with GY.…”
Section: Discussionmentioning
confidence: 94%